Construção de aplicações computacionais na saúde: explorando a abordagem Design Science Research - Davila, Nicole C.; Reis, Adriana N. dos (Anais da Escola Regional de Computação Aplicada à Saúde (ERCAS); 2018: Anais da VI Escola Regional de Computação aplicada à Saúde, 2018)
This paper presents an exploratory research about the construction of computational applications in health. The goal is evaluate studies in this field from the perspective of the Design Science Research, an approach that involves design and development of artifacts in scientific process. The study considers publications of the 17th Workshop of Medical Informatics (2017), analyzing elements presented from the perspective of the mentioned method. The results indicate that the approach can contribute to increase the consistency and accuracy of the computational work applied to health.